2011
DOI: 10.1080/08952841.2011.611052
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Relationship of Social Activity and Quality of Life in Community-Dwelling Taiwanese Elders

Abstract: This study explores the gender differences in the relationship between social activity and quality of life (QOL). A cross-sectional survey of 220 community-dwelling elderly people was conducted in southern Taiwan. Social activity was classified into six categories. The brief version of the World Health Organization QOL (WHOQOL-BREF) was used to measure QOL. Findings revealed that the associations of six types of social activities with QOL were weaker among women than men. The regression analyses further showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 37 publications
(50 reference statements)
3
25
1
Order By: Relevance
“…The study was approved by the Institutional Review Board of National Cheng Kung University Hospital before the study began. The data were derived from a cross-sectional study with a convenience sampling design described elsewhere (Li et al, 2011). In brief, 256 community-dwelling elderly Taiwanese participated between October 2007 and May 2008.…”
Section: Datamentioning
confidence: 99%
“…The study was approved by the Institutional Review Board of National Cheng Kung University Hospital before the study began. The data were derived from a cross-sectional study with a convenience sampling design described elsewhere (Li et al, 2011). In brief, 256 community-dwelling elderly Taiwanese participated between October 2007 and May 2008.…”
Section: Datamentioning
confidence: 99%
“…Therefore, there might be cohort differences that shared different social and non-social events throughout the aging process. Despite the cohort effect on the elderly population, gender differences are easily found in a society that can possibly affect the quality of life and cognitive level [38][39][40][41]. Men and women tend to participate in different social activities which could influence their quality of life and/or cognitive level [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to cognitive level, gender has a stronger association. Many studies have shown that women are at a higher risk of dementia and Alzheimer's disease [14,40,41], and their study subjects were the elderly population of various ages. Their results were consistent with the investigations conducted on gender difference on dementia and Alzheimer's disease among elders [14,[40][41][42][43], and our results exhibited a higher OR of the low cognitive function groups in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, women are given the role of caring for their families and the home, while men are given the role of provider. Thus, it is correct to think that the elderly women tend to engage in milder intensity activities, of a social nature, that include household maintenance and that are closer to the family-neighbourhood nucleus, while the elderly men, although initially more reluctant to engage, are more likely to commit to higher intensity activities and further away from this nucleus 38,39 because they are more accustomed to being involved in labour and productive activities or having better functionality 36,37 .…”
Section: Discussionmentioning
confidence: 99%